Battlestar Galactica The Miniseries - Moore, Ronald D.; Olmos, Edward James 1947-; McDonnell, Mary 1952-; Sackhoff, Katee 1980- (Universal Studios, 2004)
After 40 years absence, the Cylons return and launch a sneak attack on the colonies. The Battlestar Galactica and its fighter pilots can't prevent the colonies' obliteration. The Galactica leads survivors to find the 13th colony, a planet called Earth
Subtitles: Spanish, French. - Originally broadcast by the Sci-Fi Channel in 2003. - Based on a teleplay by Glen A. Larson; remake of the 1970s television series. - Special features: Making-of featurette 'Battlestar galactica : the lowdown'; deleted scenes; audio commentary
Keywords: Space colonies / Drama; Robots / Drama; Space warfare / Drama; Robots; Space colonies; Space warfare; Space warfare -- Drama; Interplanetary voyages -- Drama; Space vehicles -- Drama; Space colonies -- Drama; Space ships -- Drama; Science fiction television programs.; Television programs.; Television series; Krieg; Weltraum; Raumfahrzeug; Siedlung; Science-Fiction-Literatur; Fernsehserie; DVD-Video